Albania’s Internal Instability and the Position Held by the Italian Government in the Years (1920-1924) - Ibra, Dashnor (Richtmann Publishing, 2012)
The purpose of this paper is the analytical representation of the historical, political and diplomatic situation that hasaccompanied the internal political situation in Albania and the position held by the Italian Government during the years 1920-1924. The Years period 1920-1924 reflects a chaotic state of governance in Albania, characterized by a political struggle, whichhad two key figures as the protagonist of these years, Fan Noli and Ahmet Zogu. This instability was evident if we take intoaccount the fact that from January 1920 until June 1924 in Albania was formed 12 different governments. The Albanian politicalsituation appeared somewhat confused by the tightening of the contrasts between the two great currents, liberal andconservative, in which he divided the Albanian political spectrum. During this period of confrontation both political camps inAlbania made the request for support by the Italian Government. The Government of Italy during this period took a decision notto intervene in the internal affairs of Albania, and this attitude also asked to keep Yugoslavia, under the Agreement concludedwith the Belgrade Government in June 1924. The position of Italy to Albania will change after the arrival to power of Mr. AhmetZogu, who despite that came to power aided by Yugoslavia, sought to recover the good relations with Italy, from where hereceived a guarantee of economic, political and military. This assistance provided will help the country emerge from the crisis,where she was, but also would ensure its long-term power, and would be a powerful deterrent against countries like Greece andYugoslavia.